Taxation, corruption and the exchange rate regime - Carsten Hefeker (Center for Economic Studies and ifo Institute (CESifo), 2009)
The paper analyzes the relation between institutional quality, such as corruption, in a country and its monetary regime. It is shown that a credibly fixed exchange rate to a low inflation country, like a currency board, can reduce corruption and improve the fiscal system. A monetary union, however, has ambiguous effects. I find that there is convergence between countries with regard to the level of corruption.
Keywords: D72; E63; F33; 330; Exchange rate regime; monetary policy; fiscal policy; seigniorage; corruption; developing and transition countries; Politische Stabilität; Wechselkurssystem; Finanzpolitik; Inflation; Korruption; Münzgewinn; Aufstrebende Märkte; Übergangswirtschaft; Schwellenländer; Entwicklungsländer